2001
DOI: 10.1016/s0002-9440(10)63970-3
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that Furin Is an Authentic Transforming Growth Factor-β1-Converting Enzyme

Abstract: Transforming growth factor (TGF)-beta1 plays an essential role in cell growth and differentiation. It is also considered as a gatekeeper of immune homeostasis with gene disruption leading to autoimmune and inflammatory diseases. TGF-beta1 is produced as an inactive precursor polypeptide that can be efficiently secreted but correct proteolytic cleavage is an essential step for its activation. Assessment of the cleavage site has revealed a unique R-H-R-R sequence reminiscent of proprotein convertase (PC) recogni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
194
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(205 citation statements)
references
References 82 publications
3
194
0
Order By: Relevance
“…Interestingly, the data showed that the expression of only furin among all the PCs can be modulated by its cleavage product, TGF-b1, which can coordinately increase the transcription of furin and TGF-b1 precursor. Consistently, only furin is coexpressed with TGF-b1 in the developing heart, bones, and fetal liver [57]. Another study also showed that Emilin1 can inhibit TGFb1-induced signaling by preventing its furin-mediated cleavage, which is associated with decreased BP [58].…”
Section: Furin May Regulate Bp By Modulation Of Transforming Growth Fmentioning
confidence: 80%
See 2 more Smart Citations
“…Interestingly, the data showed that the expression of only furin among all the PCs can be modulated by its cleavage product, TGF-b1, which can coordinately increase the transcription of furin and TGF-b1 precursor. Consistently, only furin is coexpressed with TGF-b1 in the developing heart, bones, and fetal liver [57]. Another study also showed that Emilin1 can inhibit TGFb1-induced signaling by preventing its furin-mediated cleavage, which is associated with decreased BP [58].…”
Section: Furin May Regulate Bp By Modulation Of Transforming Growth Fmentioning
confidence: 80%
“…Then, proteolytic cleavage is required for its activation. Evaluation of the cleavage sites revealed a unique R-H-R-R sequence that is cleaved by furin [57]. In furinpositive BSC-40 cells, treatment with a1-PDX markedly blocked the maturation of TGF-b1 precursor.…”
Section: Furin May Regulate Bp By Modulation Of Transforming Growth Fmentioning
confidence: 97%
See 1 more Smart Citation
“…TGFB1 directly induces Furin expression in rodents, which is a prerequisite for its functional maturation and anti-inflammatory function (18,38). Consequently, the autoimmune phenotype of CD4cre-fur fl/fl mice can be chiefly attributed to a lack of bioavailable, T cell-produced TGFB1.…”
Section: Resultsmentioning
confidence: 99%
“…38 Besides TGF-b1 furin cleaves for example b-nerve growth factor, bone morphogenetic protein-4, membrane-type 1 matrix metalloproteinase, the a-and b-secretases associated with Alzheimer's disease and bacterial toxins. [42][43][44] Cleavage of these substrates occurs at the TGN but is not limited to this compartment. Furin cycles between the TGN and the cell surface, where it can process different substrates.…”
Section: Discussionmentioning
confidence: 99%